2020
DOI: 10.1039/c9cy02603g
|View full text |Cite
|
Sign up to set email alerts
|

The competition between dehydrogenation and dehydration reactions for primary and secondary alcohols over gallia: unravelling the effects of molecular and electronic structure via a two-pronged theoretical/experimental approach

Abstract: The relative dehydrogenation/dehydration reactivity imparted by nanostructured gallium(iii) oxide on alcohols was investigated via electronic structure calculations, reactivity tests and DRIFT-IR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
3
7
0
Order By: Relevance
“…Also, a small amount of methyl formate (MF) was observed (Y(MF) = 4.5 % at 430 °C). This product distribution is in line with previous studies on ChemCatChem methanol decomposition over β-Ga 2 O 3 at 400 °C reported by Izzo et al [36] In addition to DME, they also detected carbon oxides in the product stream, which was explained by the decomposition of either CH 2 O to CO and H 2 and of MF to CO 2 and CH 4 . The reported conversion was higher (> 95 %) despite the higher methanol concentration in the feed stream (18 %) due to the higher catalyst amount (1 g vs. 50 mg) and the longer residence time (1 s vs. < 0.11 s) in comparison to the reaction conditions in this study.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Also, a small amount of methyl formate (MF) was observed (Y(MF) = 4.5 % at 430 °C). This product distribution is in line with previous studies on ChemCatChem methanol decomposition over β-Ga 2 O 3 at 400 °C reported by Izzo et al [36] In addition to DME, they also detected carbon oxides in the product stream, which was explained by the decomposition of either CH 2 O to CO and H 2 and of MF to CO 2 and CH 4 . The reported conversion was higher (> 95 %) despite the higher methanol concentration in the feed stream (18 %) due to the higher catalyst amount (1 g vs. 50 mg) and the longer residence time (1 s vs. < 0.11 s) in comparison to the reaction conditions in this study.…”
Section: Resultssupporting
confidence: 92%
“…Also, a small amount of methyl formate (MF) was observed ( Y (MF)=4.5 % at 430 °C). This product distribution is in line with previous studies on methanol decomposition over β‐Ga 2 O 3 at 400 °C reported by Izzo et al [36] . In addition to DME, they also detected carbon oxides in the product stream, which was explained by the decomposition of either CH 2 O to CO and H 2 and of MF to CO 2 and CH 4 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The role of gallium deserves a special attention, as its position in the periodic table should impart amphoteric properties to its oxide. Gallia has been shown to be more active in dehydrogenation than in dehydration of ethanol [103]. This result is coherent with the high basicity imparted to LaAlO 3 by incorporation of gallium, as indicated by the results of isopropanol conversion on Ga25.…”
Section: Correlations Between Activity and Composition Of The Catalystssupporting
confidence: 59%
“…[13] Interestingly, gallium oxide (Ga2O3) has also proven to have a peculiar catalytic activity in the dehydrogenation of alcohols. [14] However, Ga is considered a technologically critical element, not only because of its limited production (mainly as a by-product of Al production from bauxite) but also because it finds applications in several strategic high-tech products. [15] Notably, the inclusion of small amounts of Ga as a promoter in the lattice of magnesium oxide (MgO) have proven to be sufficient for fostering in situ methanol dehydrogenation to formaldehyde, making it possible to greatly enhance the alkylation of phenol to TMP compared to MgO.…”
Section: The Evolution Of Alkylation Processesmentioning
confidence: 99%